Pelatihan penyusunan audit tatakelola resiko keuangan untuk koperasi desa: Sukolilo, Kecamatan Wajak, Kabupaten Malang, Provinsi Jawa Timur - Arief Yuswanto Nugroho; Anudiyan Amir Mas'ud; Alfira Rosadiana (JOURNAL INNOVATION AND COMMUNITY SERVICE, 2023)
Cooperatives are legal entities that generally have the aim of improving and fostering the welfare of their members, especially economically weak groups. Cooperatives as microfinance institutions are very much needed by microentrepreneurs and small and medium enterprises to be able to help advance business activities by becoming a source of funds and financing for entrepreneurs. The role and function of cooperatives are very important because banking financial institutions are still not optimal in their micro, small, and medium entrepreneur segments. Nowadays, cooperatives have a weakness, namely a lack of public trust in cooperatives, so a new strategy or paradigm is needed to build the image of cooperatives in order to improve the institutional capacity of the cooperative. One of the ways to implement a new strategy or paradigm in building the image of cooperatives is, namely, through the implementation of banking operational risk management in cooperatives. Banks can also help with the implementation and operational risks of banking for cooperatives through banking program linkages. The research method used is normative juridical, with the technique of collecting legal materials through a literature study of positive law in this case, which regulates cooperatives and banking. From the results of this research, it is known that it is possible for cooperatives to be able to implement management. Operational risks and linkage programs can be used as a means for banks to assist cooperatives in implementing risk management.